Development of hypercontent-based teaching materials for screen printing course at FIP UNM - Asrul Burhan; P. Pattaufi; Nurhikmah H; Farida Febriati; Abdul Hakim; Citra Rosalyn Anwar; W. Wahira (Inovasi Kurikulum, 2024)
This research was conducted to meet the need for hypercontent-based digital teaching materials in the Screen Printing Techniques course in the Educational Technology Study Program, FIP UNM. The existing materials are less interactive and lack media such as text, images, and videos, essential for enhancing student understanding. The main goals are identifying these needs, designing hypercontent-based digital teaching materials, and measuring their validity, practicality, and effectiveness. The Research and Development (RD) method follows the M. Alessi and Stanley R. Trollip model, including the stages of planning, design, and development. The research subjects included 20 students, one lecturer, and two validators (1 content/material expert and one design/media expert). Data collection techniques involved needs identification questionnaires, expert validation questionnaires, lecturer response questionnaires, and small and large group trial questionnaires. Descriptive quantitative analysis was used to evaluate the data. The findings indicate that the need for digital modules among students is very high, expert validation shows good qualifications, trials demonstrate the modules’ good practicality, and pre-test and post-test results reveal improved student learning outcomes with effective to very effective qualifications. Consequently, the screen printing technique digital module is deemed valid, practical, and effective. AbstrakPenelitian ini dilakukan untuk memenuhi kebutuhan akan bahan ajar digital berbasis hypercontent pada mata kuliah Teknik Sablon di Prodi Teknologi Pendidikan FIP UNM, karena bahan ajar yang ada saat ini kurang interaktif dan tidak menyediakan berbagai media seperti teks, gambar, dan video yang dapat meningkatkan pemahaman mahasiswa. Tujuan utamanya adalah mengidentifikasi kebutuhan tersebut, merancang bahan ajar digital berbasis hypercontent, serta mengukur tingkat validitas, kepraktisan, dan efektivitasnya. Metode yang digunakan adalah Research and Development (RD) dengan model M. Alessi dan Stanley R. Trollip, mencakup tahap perencanaan, desain, dan pengembangan. Subjek penelitian terdiri dari 20 mahasiswa, 1 dosen pengampu, dan 2 validator (1 ahli isi/materi dan 1 ahli desain/media). Teknik pengumpulan data meliputi angket identifikasi kebutuhan, angket validasi ahli, angket tanggapan dosen, serta angket uji coba kelompok kecil dan besar. Analisis data dilakukan secara deskriptif kuantitatif. Temuan menunjukkan bahwa kebutuhan mahasiswa terhadap modul digital sangat tinggi, validasi ahli menunjukkan kualifikasi baik hingga sangat baik, uji coba menunjukkan kepraktisan modul yang baik, dan hasil pre-test dan post-test menunjukkan peningkatan hasil belajar mahasiswa dengan kualifikasi efektif hingga sangat efektif. Modul digital Teknik Sablon dinyatakan valid, praktis, dan efektif.Kata Kunci: Modul digital; teknologi pendidikan; pengembangan bahan belajar; teknik sablon